2022
DOI: 10.1037/tra0000777
|View full text |Cite
|
Sign up to set email alerts
|

Testing theoretical predictors of posttraumatic growth and posttraumatic stress symptoms.

Abstract: Objective: The current study aimed to assess the new theoretical model of PTG, alongside a measure of posttraumatic stress symptoms (PTSS) due to the ongoing distress that is often experienced by trauma survivors. The study examined the direct pathway to PTG and PTSS through previously identified predictors including core belief disruption, event centrality, and rumination, with the addition of self-disclosure as a predictor variable. Method: Participants (N = 231) who had experienced a traumatic event were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The results of the correlation analysis presented in Table 3 show that intrusive ruminations, both during the weeks immediately after the difficult event and recently, were negatively associated with life satisfaction, which is consistent with the results of previous studies (Triplett et al, 2012; Morgan et al, 2017). Deliberate ruminations, as in previous studies (Cann et al, 2011;Triplett et al, 2012;David et al, 2021;Taku et al, 2021), were positively associated with posttraumatic growth (overall result) and with posttraumatic growth experienced in the following areas: new possibilities, appreciation of life, and spiritual and existential changes.…”
Section: Styles Of Rumination and Coping Strategies As Predictors Of ...supporting
confidence: 89%
“…The results of the correlation analysis presented in Table 3 show that intrusive ruminations, both during the weeks immediately after the difficult event and recently, were negatively associated with life satisfaction, which is consistent with the results of previous studies (Triplett et al, 2012; Morgan et al, 2017). Deliberate ruminations, as in previous studies (Cann et al, 2011;Triplett et al, 2012;David et al, 2021;Taku et al, 2021), were positively associated with posttraumatic growth (overall result) and with posttraumatic growth experienced in the following areas: new possibilities, appreciation of life, and spiritual and existential changes.…”
Section: Styles Of Rumination and Coping Strategies As Predictors Of ...supporting
confidence: 89%
“…Previous research provided support for applicability of this theory to women who have experienced miscarriage or stillbirth as core belief challenge was a strong predictor of PTG and the relationship between core belief challenge and PTG was mediated by deliberate rumination (Freedle & Kashubeck-West, 2021). Therefore, further research should include all predictive components of the theory in the model to better understand the process of PTG (David et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with other bereaved and stigmatized populations showed that self-disclosure positively contributed to PTG levels, concluding that it may play an important role in facilitating PTG (Levi-Belz, 2019). More recently, using a convenience sample, David et al (2021) found that for disclosure to predict PTG, it needs to be perceived as helpful. Feeling relief, having a greater understanding of the event, or finding it easier to resolve what happened was the strongest predictor of PTG (David et al, 2021).…”
Section: Self-disclosure Rumination and Ptgmentioning
confidence: 99%
“…Greater event centrality and deliberate rumination result both more distress and more growth (David et al, 2022). The distinction is that growth only occurs if meaning is found; survivors with high event centrality and frequent rumination who do not find meaning will experience continued or increased traumatic stress (David et al, 2022; Park, 2010; Tedeschi et al, 2018). In summary, the process of meaning-making around traumas with high centrality fits the empirical findings that PTG is most prevalent alongside some (but not severe) distress; event centrality explains why the PTS–PTG relationship varies across traumas of different severities.…”
Section: Curvilinear Relationships Between Ptg and Symptomsmentioning
confidence: 99%